Catchment controls on solute export. (December 2015) - Musolff, Andreas; Schmidt, Christian; Selle, Benny; Fleckenstein, Jan H.
Highlights: Concentration and discharge time series of nine catchments have been investigated. Simple metrics of the C – Q relations allow for the classification of export regime. Metrics of export regime can be predicted from catchment characteristics. Abstract: Dynamics of solute export from catchments can be classified in terms of chemostatic and chemodynamic export regimes by an analysis of concentration–discharge relationships. Previous studies hypothesized that distinct export regimes emerge from the presence of solute mass stores within the catchment and their connectivity to the stream. However, so far a direct link of solute export to identifiable catchment characteristics is missing. Here we investigate long-term time series of stream water quality and quantity of nine neighboring catchments in Central Germany ranging from relatively pristine mountain catchments to agriculturally dominated lowland catchments, spanning large gradients in land use, geology, and climatic conditions. Given the strong collinearity of catchment characteristics we used partial least square regression analysis to quantify the predictive power of these characteristics for median concentrations and the metrics of export regime. We can show that median concentrations and metrics of the export regimes of major ions and nutrients can indeed be inferred from catchment characteristics. Strongest predictors for median concentrations were the share of arable land, discharge per area, runoff coefficient and available water capacity in the root zone of the catchments. The available water capacity in the root zone, the share of arable land being artificially drained and the topographic gradient were found to be the most relevant predictors for the metrics of export regime. These catchment characteristics can represent the size of solute mass store such as the fraction of arable land being a measure for the store of nitrate. On the other hand, catchment characteristics can be a measure for the connectivity of these solute stores to the stream such as the fraction of tile drained land in the catchments. This study demonstrates the potential of data-driven, top down analyses using simple metrics to classify and better understand dominant controls of solute export from catchments. Graphical abstract: